Incompatible european partners? Cultural predispositions and household financial behavior - Michael Haliassos; Thomas Jansson; Yigitcan Karabulut (Sveriges Riksbank, 2014)
The Eurozone fiscal crisis has created pressure for institutional harmonization, but skeptics argue that cultural predispositions can prevent convergence in behavior. Our paper derives a robust cultural classification of European countries and utilizes unique data on natives and immigrants to Sweden. Classification based on genetic distance or on Hofstede's cultural dimensions fails to identify a single 'southern' culture but points to a 'northern' culture. Significant differences in financial behavior are found across cultural groups, controlling for household characteristics. Financial behavior tends to converge with longer exposure to common institutions, but is slowed down by longer exposure to original institutions.
Keywords: G11; E21; 330; Household Portfolios; Household Finance; Cultural Influences on Economic Behavior